The perception of social workers on the implications of Artificial Intelligence in their professional practices: An exploratory study - García González, Paula; Morales Hernández, Ana; Cáceres Rodríguez, Celsa (Cuadernos de Trabajo Social, 2025)
The field of Artificial Intelligence (AI) has advanced considerably, finding applications in various sectors, including Social Work. The purpose of this research is to explore the perception of social workers regarding the use of AI in their professional practices, focusing on its knowledge, usage and ethical implications. To this end, an ad hoc questionnaire was administered to 120 social workers. The results reveal that general knowledge about AI among social workers is limited and its implementation is still incipient, despite the potential benefits identified. The willingness to use AI applications is much lower in direct intervention functions than in indirect ones. The greatest risk is perceived in the possibility that IA applications might affect decision-making capacity. The conclusions highlight the need to provide training on AI to ensure responsible and effective implementation, guaranteeing adherence to ethical principles.